2019
DOI: 10.4315/0362-028x.jfp-18-529
|View full text |Cite
|
Sign up to set email alerts
|

Freshness Evaluation in Chub Mackerel (Scomber japonicus) Using Near-Infrared Spectroscopy Determination of the Cadaverine Content

Abstract: We analyzed the volatile basic nitrogen content, pH, total viable cell count, and biogenic amine contents in chub mackerel (Scomber japonicus) stored at 5 and 25°C to examine changes in freshness. Among the various parameters, we found the volatile basic nitrogen content had the highest correlation with cadaverine content (r2 = 0.72 to 0.88). We also tried to measure cadaverine contents at different times during storage by using near-infrared (NIR) spectroscopy. However, because of the high water content in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…An expanding array of studies have indicated the application of NIR in fish products. For instance, researchers found that NIR spectroscopy uses biogenic amine content to quickly and accurately assess fish freshness (R 2 = 0.98) [101]. In addition, researchers have used near-infrared spectroscopy in the 800-2500 nm region to predict the potential of bacterial populations in salmon stored at 4 • C. The PLSR model was built on 72 data points and predicted the total number of aerobic slabs for the calibration and validation datasets with R 2 values of 0.95 and 0.64, respectively [102].…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%
“…An expanding array of studies have indicated the application of NIR in fish products. For instance, researchers found that NIR spectroscopy uses biogenic amine content to quickly and accurately assess fish freshness (R 2 = 0.98) [101]. In addition, researchers have used near-infrared spectroscopy in the 800-2500 nm region to predict the potential of bacterial populations in salmon stored at 4 • C. The PLSR model was built on 72 data points and predicted the total number of aerobic slabs for the calibration and validation datasets with R 2 values of 0.95 and 0.64, respectively [102].…”
Section: Near-infrared Spectroscopymentioning
confidence: 99%
“…NIRS has been used as a tool to determine the cadaverine content in homogenized and ultrafiltered solutions of Chub Mackerel (Scomber japonicus) stored at different temperatures (5 and 25°C) [80]. The r 2 obtained in the regression analysis was 0.98 and 0.99 for the different dilutions made.…”
Section: Detection Of Spoilage Compoundsmentioning
confidence: 99%
“…Near infrared spectroscopy (NIR) has drawn considerable interest for many reasons, including its portability, speed, cost-effectiveness, suitability for in-line as well as on-line analysis, and the ability to concurrently measure different parameters for a large number of samples [151][152][153][154][155][156][157]. Several studies reported on the use of NIR for meat quality assessment and the analyses of meat properties in live animals or carcasses due to the capability of IR light to penetrate several layers of tissue [151][152][153][154][155][156][157][158][159]. Two published papers demonstrated that the short wavelength radiation in the NIR region of the electromagnetic spectrum can potentially be utilized to non-invasively assess meat quality [152,154].…”
Section: Nir Spectroscopy In Meat and Meat Products Fish And Seafoomentioning
confidence: 99%
“…Kilbo et al [158] have demonstrated the ability of NIR based methods to rapidly and precisely determine biogenic amine content as the same could be used to evaluate the freshness of fish and poultry products. The authors, however, have pointed out that dehydrated samples must be prepared, following procedures that they have developed, as the developed NIR method is not suitable for the samples with high water content.…”
Section: Nir Spectroscopy In Meat and Meat Products Fish And Seafoomentioning
confidence: 99%